Women's Resilience Regarding Otang Tengka Tradition In Besuki Village, East Java - Faridatur Riskiyah; Alifiulahtin Utaminingsih; Siti Kholifah (Musãwa Jurnal Studi Gender dan Islam, 2024)
Otang tengka is a Madurese ethnic tradition synonymous with the role of married women in giving and receiving donations from groceries to those with special needs, such as for births, marriages, and even funerals. In practice, this tradition imposes economic demands as there is an obligation to participate in donation activities, mainly when the community's financial condition is middle to lower. This study aims to identify the forms of resilience developed by women who play essential roles in carrying out traditions, especially in Besuki Village, Besuki District, Situbondo Regency, East Java – the focus of this research. Bonnie Benard's resilience theory examines the various forms of women's resilience. This study adopts qualitative research methods, utilizing observation and interviews for data collection. The findings indicate several forms of resilience developed by married women, including engaging in trade as a form of autonomy, negotiating as a problem-solving strategy, managing family finances as an expression of purpose and future orientation, and socializing as a manifestation of a sense of humor. [ Otang tengka merupakan tradisi etnis Madura yang identik dengan peran perempuan yang sudah menikah dalam proses pemberian dan penerimaan sumbangan berupa sembako kepada pihak yang memiliki hajat berupa kelahiran, pernikahan, hingga kematian. Pada praktiknya, tradisi ini memberikan tuntutan secara ekonomi karena adanya kewajiban mengikuti kegiatan sumbang-menyumbang sementara kondisi ekonomi masyarakat adalah menengah ke bawah. Penelitian ini bertujuan untuk mengetahui bentuk-bentuk resiliensi yang dikembangkan oleh perempuan selaku aktor penting dalam pelaksanaan tradisi terutama di Desa Besuki, Kecamatan Besuki, Kabupaten Situbondo, Jawa Timur sebagai lokasi penelitiannya. Teori resiliensi dari Bonie Benard digunakan untuk melihat bentuk-bentuk dari resiliensi perempuan. Penelitian ini menggunakan metode penelitian kualitatif dengan teknik pengumpulan data berupa observasi dan wawancara. Hasil penelitian menunjukkan bahwa terdapat beberapa bentuk resiliensi yang dikembangkan oleh perempuan yang sudah menikah, yaitu berdagang sebagai bentuk autonomi, negosiasi sebagai bentuk problem solving, pengelola keuangan keluarga sebagai bentuk sense of purpose and future, dan bersosialisasi sebagai bentuk sense of humor.]